ANALISIS KEGIATAN PEMBELAJARAN KOMUNITAS HARAPAN PADA ANAK-ANAK USIA SEKOLAH DASAR DI KAWASAN KAMPUNG SUMENEBAN, PASAR JOHAR SEMARANG - Sinta Salsabela (STKIP Subang, 2022)
Marginal environments such as in the market area which is a slum area in which deviant behaviors are often found violating social norms. The Komunitas Harapan is here to provide improvements to the surrounding environment, namely by providing various positive activities for children. This study aims to analyze the process of learning activities for elementary school-aged children, volunteers who participate in the Komunitas Harapan, the obstacles and benefits of learning activities in the Komunitas Harapan. This research method uses a qualitative descriptive approach. The subjects in this study were elementary school-age children in the Komunitas Harapan, volunteers from the Komunitas Harapan, their parents, and the founder of the Komunitas Harapan. Data collection techniques through observation, interviews, and documentation. The validity of the data in this study used a triangulation method. The results of this study are learning activities are carried out every Thursday, Friday, Saturday, and Sunday. For Thursdays and Sundays are subject matter learning, Friday reading activities, and Saturday learning English. This learning activity is carried out by volunteers or speakers from outside the Komunitas Harapan. Volunteers consist of students from various universities and the community who are already working. The benefits of this learning activity are to make children more active, increase knowledge, and increase experience. The obstacle is that there are fewer volunteers because they do not experience adequate regeneration and problems with learning places.